Biodiversity of the ants (insecta: hymenoptera) associated with the center agroecosystems of Argentina - Pall, José Luis María (2014)
The world change in land use and crop modification has been, at the expenses of forests, pastures and swamps. Argentina pampean plains have not been an exception because of this global tendency with an agricultural border continuous advance from the east to the semiarid west. This generates a loss of biological diversity that affects a great number of organisms among which we find the ants, which play a very important role in the communities structure doing a balance between living creatures and their habitat. The aim of this work is compare the myrmecofauna associated with productive agroecosystems in the central region of Argentina, through the evaluation richness of these insects and diversity. The hypothesis of this study is to test the diversity of Formicidae in fields where little anthropogenic is greater than in agroecosystems of central Argentina. Three farms were chosen as study sites, each of them divided into two sampling sites that correspond to cultivated or natural areas. A total of 5.647 ants were collected among which three dominant species were found in all the sites: Dorymyrmex breviscapis, Solenopsis saevissima and Pheidole bergi. Significant differences were observed between the agroecosystems myrmecofauna and the natural environments.